Peningkatan Hasil Belajar Geometri Menggunakan Model Problem Based Learning di Kelas V SDN 18 Tebing Tinggi Kabupaten Pesisir Selatan - Berlian Selvina Putri; Melva Zainil (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe how to improve students' learning outcomes in Geometry learning using the Problem Based Learning model in class V of SDN 18 Tebing Tinggi, Pesisir Selatan Regency. This type of research is classroom action research (PTK) using qualitative and quantitative approaches which are carried out in two cycles, with research procedures. The results of the study showed an increase in geometry learning outcomes from cycle I to cycle II. The results of the observation of the teaching module in the first cycle of the first meeting were obtained 79% (C) then in the first cycle of the second meeting the result of 87% (B) for that the observation of the first cycle of the teaching module was obtained an average of 83% (B), increasing in the second cycle to 95% (SB). Second, the results of the observation of the implementation of teacher aspect learning in the first cycle of the first meeting obtained a result of 78% (C), then in the first cycle of the second meeting obtained a result of 86% (B) for that the results of the observation of the teacher aspect obtained an average of 82% (B), increasing in the second cycle to 93% (SB). Third, the results of the implementation of learning aspects of students in the first cycle of meeting I obtained a result of 78% (C), then in the first cycle of meeting II obtained a result of 86% (B) for that the results of observation of the student aspect obtained an average of 82% (B), increasing in the second cycle to 93% (SB). Fourth, the learning outcomes of students in the first cycle of meeting I were obtained with a result of 71 (C), then in the first cycle of meeting II a result of 81 (B) for that the learning results of the first cycle were obtained an average of 76 (C), increasing in the second cycle to 90 (SB). Thus, it can be concluded that the Problem Based Learning model can improve students' learning outcomes in Geometry learning in grade V of SDN 18 Tebing Tinggi, South Pesisir Regency